Identification of Critical Thinking Skills in Physics Based on Students Thinking Style in Class XI SMAN 5 Wajo - Rosdiana, Rosdiana; Usman, Usman; Hasyim, Mutahharah; Setiawan, Trisno (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2025)
This research is a quantitative study which aims to determine the description of critical thinking abilities in physics in terms of students' thinking styles. The thinking styles that will be used in this research are concrete sequential, abstract sequential, concrete random, and abstract random thinking styles. The sample in this research was all 37 students in class XI of SMAN 5 Wajo. Data collection techniques use thinking style tests and physics critical thinking ability tests. The thinking style instrument used in this research is an instrument developed by De Porter which consists of 15 numbers with four answer choices. Meanwhile, students' critical thinking abilities are in the form of test instruments. The research data were analyzed using descriptive statistical analysis, data presentation and drawing conclusions. Based on the results of data analysis, it was found that students who had a dominant concrete sequential thinking style had the critical thinking category, students who had a dominant abstract sequential thinking style had a level of critical thinking ability in the very critical category, while students who had a dominant concrete random thinking style had The level of critical thinking ability is in the non-critical category, and students who have a dominant abstract random thinking style have the level of critical thinking ability in the moderately critical category.